2016
DOI: 10.1021/acs.joc.6b01219
|View full text |Cite
|
Sign up to set email alerts
|

Defying Stereotypes with Nanodiamonds: Stable Primary Diamondoid Phosphines

Abstract: Direct unequal C-H bond difunctionalization of phosphorylated diamantane was achieved in high yield from the corresponding phosphonates. Reduction of the functionalized phosphonates provides access to novel primary and secondary alkyl/aryl diamantane phosphines. The prepared primary diamantyl phosphines are quite air stable compared to their adamantyl and especially alkyl or aryl analogues. This finding is corroborated by comparing the singly occupied molecular orbital energy levels of the corresponding phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 61 publications
(154 reference statements)
2
18
0
Order By: Relevance
“…(9‐Hydroxydiamant‐4‐yl)phosphonic dichloride (L2) : Obtained analytical data were identical to the literature data …”
Section: Methodssupporting
confidence: 67%
See 2 more Smart Citations
“…(9‐Hydroxydiamant‐4‐yl)phosphonic dichloride (L2) : Obtained analytical data were identical to the literature data …”
Section: Methodssupporting
confidence: 67%
“…Conversely, primary diamantyl phosphines L6 and L7 displayed activities comparable to that of L1 . We already reported that electron‐withdrawing functions at remote positions of the diamantane cage are essential to enhance air‐stability in the solid state of primary diamantyl phosphines …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We surprisingly found for this purely organic phosphine a S BET =138 m 2 g −1 , which is significantly higher than several reported porous composite materials . Accordingly, we measured the surface area of (9‐hydroxydiamant‐4‐yl)phosphonic dichloride ( 5 , named Cl 2 (O)P‐DiamOH) and its chlorinated analogue (9‐chlorodiamant‐4‐yl)phosphonic dichloride ( 6 , Cl 2 (O)P‐Diam‐Cl) to found much lower values S BET =40 and 25 m 2 g −1 , respectively (Supporting Information, Figure S5d). While single crystals of 5 could not be obtained, the XRD structure of Cl 2 (O)P–DiamCl, clearly reveals no voids.…”
Section: Figurementioning
confidence: 53%
“…Accordingly, we measured the surface area of (9‐hydroxydiamant‐4‐yl)phosphonic dichloride ( 5 , named Cl 2 (O)P‐DiamOH) and its chlorinated analogue (9‐chlorodiamant‐4‐yl)phosphonic dichloride ( 6 , Cl 2 (O)P‐Diam‐Cl) to found much lower values S BET =40 and 25 m 2 g −1 , respectively (Supporting Information, Figure S5d). While single crystals of 5 could not be obtained, the XRD structure of Cl 2 (O)P–DiamCl, clearly reveals no voids. A S BET =54 m 2 g −1 was found for the oxide H 2 (O)P–DiamOH, 2 .…”
Section: Figurementioning
confidence: 99%